Experimental study on the seismic behavior of precast concrete column with grouted corrugated sleeves and debonded longitudinal reinforcements. Issue 15 (November 2019) - Chen, Jun; Zhao, Chenhui; Ding, Faxing; Xiang, Ping
The seismic performance and the influence of debonded longitudinal reinforcements at the footing on the precast concrete columns connected with the embedded grouted corrugated sleeve were investigated experimentally in this research. Low cyclic loading tests were carried out on eight bending columns and four shear columns, considering the designed parameters of the partial debonding of the longitudinal reinforcements above the column–foundation interface, the axial load index, and the strength of the stirrups. Experimental results indicate that the partial debonding of the longitudinal reinforcements heavily influenced the damage spreading of the bending columns, but does not affect the damages of the shear columns. Compared to the columns without debonded longitudinal reinforcements, the seismic behaviors in terms of the ductility and energy dissipation can be improved clearly by the partial debonding of the longitudinal reinforcements for bending columns, but there was no clear improvement for shear columns. In addition, with the decrease of the axial load index or the increase of the strength of the stirrups, the seismic behaviors of the precast columns with the partial debonding of the longitudinal reinforcements are improved largely.